Cluster-Mentoring for Sustainable Competency: A Case Study of PTK Training for Islamic Education Teachers in Junior High Schools - Sabarudin; Muhammad Nurul Mubin; Maksim Kim; Arifah Fauziah (Yogyakarta: Jurusan Pendidikan Agama Islam Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2023)
Purpose – Given the various challenges faced by teachers in making PTK reports, this study aims to investigate the effectiveness of the Cluster-Mentoring-based mentor program in supporting the sustainability of competency programs for Islamic Education teachers at the Junior High School level in Sleman District. Design/methods/approach – This case study evaluated the implementation of a Cluster-Mentoring-supported PTK training program among Islamic education teachers from 14 secondary schools participating in the PTK and Mendeley training using observations, online interviews, and documentation for data collection, by applying purposive sampling techniques. Findings – This study aims to improve the understanding of Islamic Education teachers in Sleman District about PTK preparation for junior high school, using Zoom meeting-based online training and Cluster-Mentoring methods and practices. The training was practical, with 63% of teachers having no difficulty finding research problems, 57% having no difficulty creating background problems, and 70% finding Mendeley app training easy to understand. After Mendeley’s training, 87.5% of trainees were able to use the app to create writing references. Cluster-Mentoring Grouping also helped participants understand the material better. Research implications/limitations – This study only focuses on variables related to PTK training programs, specifically the Cluster-Mentoring model and training outcomes. The study did not analyze other variables, such as teacher obstacles and attitudes. Originality/value – This study aims at providing an overview of competency development programs through PTK training assistance and delays using the Cluster-Mentoring method for Islamic Education teachers in Secondary Schools in Sleman.